Building power through knowledge: designing Boston's participatory budgeting process as a popular education tool - Shively, John. (Tufts University. Tisch Library., 2023)
Thesis (M.A.)--Tufts University, 2023.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Penn Loh.; Committee: May Louie.; Keyword: Public policy.